The Effectiveness of Cognitive Behavioral Therapy on Marital Control and Emotional Regulation Difficulties in Married Women with Family Problems - Karimi Panah, Sara; Pahlavani, Mari; Ehsanfar, Maryam; Anbardar, Nastaran; Rajabzade Dezfouli, Zohre (Psychology of Woman Journal, 2023)
Objective: The aim of the present study was to determine the effectiveness of Cognitive Behavioral Therapy (CBT) on marital control and emotional regulation difficulties in married women with family problems. Methods and Materials: This research employed a quasi-experimental method with a pretest-posttest design and a control group. The statistical population of this study included married women with family problems who visited counseling centers in Tehran in 2022. Subsequently, 30 married women with family problems were selected through convenience sampling and were randomly assigned to the experimental group (15 participants) and the control group (15 participants). Data collection tools included questionnaires on marital control and emotional regulation difficulties. The experimental group underwent eight sessions (two sessions per week), with each session lasting two hours, while the control group did not receive any intervention. After the completion of the intervention period, both groups were re-evaluated (post-test). Data were analysed via SPSS-25 and analysis of covariance method. Findings: The findings indicated that the mean scores of marital control and emotional regulation difficulties in the post-test of the experimental group were significantly different from those of the control group. Conclusion: Therefore, it can be concluded that Cognitive Behavioral Therapy affects marital control and emotional regulation difficulties in married women with family problems.